Floristic composition and carbon sequestration of traditional agroforestry on peatland in Rimbo Panjang, Kampar, Riau, Indonesia - MAYTA NOVALIZA ISDA; SITI FATONAH; YULMINARTI YULMINARTI; NUR ZARAH OKTARINA; DEWI INDRIYANI ROSLIM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Isda MN, Fatonah S, Yulminarti, Oktarina NZ, Roslim DI. 2025. Floristic composition and carbon sequestration of traditional agroforestry on peatland in Rimbo Panjang, Kampar, Riau, Indonesia. Biodiversitas 26: 470-479. Trees in agroforestry systems contribute to long-term carbon sequestration, helping to mitigate climate change. Traditional agroforestry is characterized by multifunctionality through the use a variety of native trees to maintain ecological balance and support local livelihoods. This study aimed to determine the plant composition of traditional agroforestry in Rimbo Panjang Village, Kampar, Riau, Indonesia, its utilization, and its role in carbon sequestration. Observations were made in two hamlets, namely Dusun 1 and Dusun 2, where both hamlets have traditional agroforestry systems. Observation on floristic composition was conducted by counting the number of individuals of each species and the diameter at breast height of each individual plant. Carbon sequestration was calculated based on the above-ground biomass determined using an allometric formula accounting for trunk diameter and wood density. The results showed that traditional agroforestry in Dusun 2 had a higher number of plant species, with a total of 17 species, compared to Dusun 1, which had 11 species. The dominant species in Dusun 1 was Cocos nucifera, while in Dusun 2 was Durio zibethinus. Plants in this agroforestry system have a variety of benefits, both for self-consumption and being marketed for domestic uses and as industrial raw materials. The average carbon sequestration in Rimbo Panjang Village was 508.65 tons/ha CO2 equivalent (CO2e), with carbon sequestration in Dusun 2 (618,3 tons/ha CO2e) higher than that of Dusun 1 (399 tons/ha CO2e). The high plant diversity in this agroforestry system supports community livelihoods and plays an important role in climate change mitigation through its role in carbon sequestration. These benefits highlight the need to support and develop sustainable agroforestry practices as a sustainable land use strategy, especially in Riau's extensively degraded peatlands.